2009
DOI: 10.2217/pgs.09.92
|View full text |Cite
|
Sign up to set email alerts
|

GRK5 Gln41Leu Polymorphism is not Associated with Sensitivity to β 1 -Adrenergic Blockade in Humans

Abstract: Aims A common, functionally significant polymorphism in GRK5 (Gln41Leu) encodes a gain-of-function enzyme that enhances desensitization of the β1-adrenergic receptor. GRK5 Leu41 has been postulated to confer endogenous ‘genetic β-blockade’ and contribute to an attenuated response to β-blockers in black subjects. The effects of this GRK5 variant on sensitivity to a β-blocker have not been studied in humans. We hypothesized that the GRK5 Gln41Leu variant contributes to interindividual variability in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The exercise protocol was well standardized and previously described in detail [10,12,13]. On the morning (8:00–10:00 am) of the study day, subjects were admitted to a temperature-controlled room (22–23°C) in the Vanderbilt University Clinical Research Center after an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…The exercise protocol was well standardized and previously described in detail [10,12,13]. On the morning (8:00–10:00 am) of the study day, subjects were admitted to a temperature-controlled room (22–23°C) in the Vanderbilt University Clinical Research Center after an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…replicated in a recent study, leaving the significance of the Gln41Leu polymorphisms unsettled (Kurnik et al, 2009). …”
Section: Ctgf-induced Desensitization Of B-arsmentioning
confidence: 95%
“…It is suggested that this genetic variation explains the fact that treatment with β-blockers for heart failure patients is more effective for Caucasians than for African Americans. However, another group reported that Leu41Gln polymorphism of GRK5 is not associated with sensitivity to a β-AR blockade in humans (Kurnik et al, 2009). They also showed that Leu41Gln variation does not contribute to the ethnic difference in sensitivity between African American and Caucasian populations to the β-blocker atenolol.…”
Section: Polymorphism Of Grk5mentioning
confidence: 97%